2023
DOI: 10.1111/aphw.12435
|View full text |Cite
|
Sign up to set email alerts
|

The positive effects of online group singing on psycho‐physiological variables during the COVID‐19 pandemic—A pilot randomized controlled trial

Abstract: The psychological variables that were particularly influenced by social distancing during the COVID‐19 pandemic—stress, loneliness, social participation, and well‐being—correspond closely to variables that can also be influenced by music. The present study is a pilot randomized controlled trial examining the effects of online group singing on psycho‐physiological variables during the pandemic. Over 4 weeks, an online singing group sang together once a week, for 1 h, under the guidance of a professional voice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…It further encourages them to communicate, coordinate their actions, and cooperate with one another, thereby leading to increased social cohesion. Schäfer (2023) tested if these and similar insights apply to audiovisual online group singing as well and found that it positively impacts feelings of social participation and can reduce experiences of loneliness. 13 In Schäfer's study, the participants could see each other as a video tile on the screen and it was thus possible for them to adjust and coordinate their physical movements with those of the others.…”
Section: (Shared) Physical Engagementmentioning
confidence: 95%
“…It further encourages them to communicate, coordinate their actions, and cooperate with one another, thereby leading to increased social cohesion. Schäfer (2023) tested if these and similar insights apply to audiovisual online group singing as well and found that it positively impacts feelings of social participation and can reduce experiences of loneliness. 13 In Schäfer's study, the participants could see each other as a video tile on the screen and it was thus possible for them to adjust and coordinate their physical movements with those of the others.…”
Section: (Shared) Physical Engagementmentioning
confidence: 95%